Use of Faecal Transplantation with a Novel Diet for Mild to Moderate Active Ulcerative Colitis: The CRAFT UC Randomised Controlled Trial. (13th September 2021) - Sarbagili Shabat, Chen; Scaldaferri, Franco; Zittan, Eran; Hirsch, Ayal; Mentella, Maria Chiara; Musca, Tania; Cohen, Nathaniel Aviv; Ron, Yulia; Fliss Isakov, Naomi; Pfeffer, Jorge; Yaakov, Michal; Fanali, Caterina; et al.
Abstract: Background: We evaluated whether integration of novel diets for donors and patients, in addition to faecal transplantation [FT], could increase FT remission rate in refractory ulcerative colitis [UC]. Methods: This was a blinded, randomised, controlled trial in adults with active UC, defined by a simple clinical colitis activity index [SCCAI] of ≥5 and ≤11 and endoscopic Mayo score 2–3, refractory to medication. Group 1 received free diet and single donor standard FT by colonoscopy on Day 1and rectal enemas on Days 2 and 14 without dietary conditioning of the donor. Group 2 received FT as above but with dietary pre-conditioning of the donor for 14 days and a UC Exclusion Diet [UCED] for the patients. Group 3 received the UCED alone. The primary endpoint was Week 8 clinical steroid-free remission, defined as SCCAI <3. Results: Of 96 planned patients, 62 were enrolled. Remission Week 8 Group 1 was 2/17 [11.8%], Group 2 was 4/19 [21.1%], Group 3 was 6/15 [40%] [non-significant]. Endoscopic remission Group 1 was 2/17 [12%], Group 2 was 3/19 [16%], Group 3 was 4/15 [27%] [Group 1 vs 3 p  = 0.38]. Mucosal healing [Mayo 0] was achieved only in Group 3 [3/15, 20%] vs 0/36 FT patients [ p  = 0.022]. Exacerbation of disease occurred in 3/17 [17.6%] of Group 1, 4/19 [21.1%] of Group 2, and 1/15 [6.7%] of Group 3 [Group 2 vs 3, p  = 0.35]. Conclusions: UCED alone appeared to achieve higher clinical remission and mucosal healing than single donor FT with or without diet. The study was stopped for futility by a safety monitoring board.